2014
DOI: 10.1590/1414-462x201400010006
|View full text |Cite
|
Sign up to set email alerts
|

Qualidade da dieta e fatores associados em crianças matriculadas em uma escola municipal de Itajaí, Santa Catarina

Abstract: ResumoO estudo teve como objetivo avaliar a qualidade da alimentação e fatores associados em escolares do primeiro ao quinto ano de uma escola municipal de Itajaí, Santa Catarina. A qualidade da dieta foi analisada por meio de um índice que conferia pontuação a cada item alimentar conforme sua frequência de consumo. Variáveis socioeconômicas, demográficas e comportamentos relacionados à saúde foram identificados por questionário. Foram calculadas razões de prevalência (RP) brutas e ajustadas, e respectivos int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
13
2
13

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(31 citation statements)
references
References 21 publications
2
13
2
13
Order By: Relevance
“…The mean score observed among students of Vitória was of 4.3 points, while in the present study the mean was of 6.0 points, and the score range attained more positive scores (-9 to +14 and -4 to +16, respectively). The mean total ALES index score in this sample was more similar to those presented by Momm & Höfelmann (2014), who evaluated the diet of 523 public schoolchildren aged 6 to 15 years, from Itajaí (Santa Catarina), with a mean score of 6.9 ranging from -9 to +17 points.…”
Section: Discussionsupporting
confidence: 77%
See 2 more Smart Citations
“…The mean score observed among students of Vitória was of 4.3 points, while in the present study the mean was of 6.0 points, and the score range attained more positive scores (-9 to +14 and -4 to +16, respectively). The mean total ALES index score in this sample was more similar to those presented by Momm & Höfelmann (2014), who evaluated the diet of 523 public schoolchildren aged 6 to 15 years, from Itajaí (Santa Catarina), with a mean score of 6.9 ranging from -9 to +17 points.…”
Section: Discussionsupporting
confidence: 77%
“…The low consumption of vegetables is also described in other studies (Molina et al, 2010b;Michereff et al, 2014) that employed ALES index with schoolchildren. Unlike found in other studies (Momm & Höfelmann, 2014;Michereff et al, 2014), in this study girls had less chance of having a poor diet quality. Molina et al (2010b) and Michereff et al (2014) concluded that low maternal education is a variable linked to poor quality of diet.…”
Section: Discussioncontrasting
confidence: 75%
See 1 more Smart Citation
“…Research suggests that highquality diet is directly associated with higher educational levels and income. 9,10 There is evidence linking the occurrence of overweight in childhood and early development of diabetes mellitus, cardiovascular disease, dyslipidemia, and hypertension in adult life. 11 Thus, childhood is a crucial period for the prevention of NCDs by encouraging and adopting healthy habits that tend to persist during adult life.…”
Section: Introductionmentioning
confidence: 99%
“…A qualidade inadequada da alimentação de crianças sofre influência de vários fatores, incluindo a menor escolaridade do cuidador e/ ou responsável, o hábito de realizar as refeições em frente à televisão, falta de atividade física e a própria avaliação negativa dos responsáveis sobre a alimentação das crianças. As atitudes dos pais em relação à alimentação dos filhos são importantes para fomentar práticas saudáveis de alimentação 20 .…”
Section: Discussionunclassified